FoMO, Facebook Addiction, and Loneliness as Determinants of Phubbing in University Students from Lima - Correa-Rojas, Jossué (2022)
Phubbing is a communication disturbance that consists in snubbing the company of another person by paying attention to one’s mobile phone. It is common in young people and has implications for the quality of social interaction. The aim of the study was to determine the relationship between Fear of Missing Out (FoMO), Facebook addiction, feelings of loneliness, age, and phubbing. Using convenience sampling, 209 students from a private university in Lima, Peru, were selected. Their ages ranged from 17 to 37 years, with a mean age of 21.28 years (SD = 3.42). Most were women (64.1%). The study adopted an explanatory design. The Phubbing Scale, the FoMO Scale, the Bergen Facebook Addiction Scale, and the Jong Gierveld Loneliness Scale were administered. The data were analyzed through Pearson’s linear correlation coefficients and a linear regression model, which showed that FoMO and Facebook addiction have direct effects on phubbing; that age has indirect effects on its variance; and that loneliness does not significantly explain this behavior.